HUBUNGAN TIPE KEPRIBADIAN DAN KONFORMITAS KELOMPOK DENGAN PERILAKU BULLYING PADA SISWA DI SMP PGRI PEKANBARU - Eninta, Mentari "; Nauli, Fathra Annis; Woferst, Rismadefi " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Bullying is recognized as a serious issue in the lives of children in school. Bullying is negative behavior that cause inconvenience to someone. This research was aimed to obtain the correlation between the personality type and the group conformity with bullying behavior of the students of Junior High School PGRI Pekanbaru which was designed into descriptive correlation and cross sectional approach. There was 212 respondents as the samples of this research that were taken based on the inclusion’s criteria by using proportionate stratified random sampling technique. The measuring instrument used in this research was the questionnarre for the personality type variable, the group conformity variable, and the bullying behavior variable. The data analyses used were univariate analysis in case of obtaining the distribution of frequency and bivariate analysis by using Chi-Square test. The research of correlation between the personality type with bullying behavior showed P value = 0,017 < α = (0,05), so it could be concluded that there was a significant correlation between the personality type and bullying behavior of the students of junior high school PGRI Pekanbaru. The research of correlation between the group conformity with bullying behavior showed P value = 0,219 > α = (0,05), so it could be concluded that there was no significant correlation between the group conformity and bullying behavior of the students of Junior High School PGRI Pekanbaru. The research can be used as a base of information and increase knowledge about personality type, group conformity, and bullying behavior, as well as a reference to bullying behavior that was happening in the community especially of the students of junior High School PGRI Pekanbaru Key words             : Bullying behavior, group conformity, personality type,